2010
DOI: 10.3390/sym2031510
|View full text |Cite
|
Sign up to set email alerts
|

Behind the Looking-Glass: A Review on Human Symmetry Perception

Abstract: The human visual system is highly proficient in extracting bilateral symmetry from visual input. This paper reviews empirical and theoretical work on human symmetry perception with a focus on recent issues such as its neural underpinnings. Symmetry detection is shown to be a versatile, ongoing visual process that interacts with other visual processes. Evidence seems to converge towards the idea that symmetry detection is subserved by a preprocessing stage involving spatial filters followed by information integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
145
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(161 citation statements)
references
References 121 publications
(210 reference statements)
7
145
2
3
Order By: Relevance
“…Psychologists measured that e.g. mirror symmetry is a very fast and important grouping mechanism for pictorial data in human observers, see (Sassi et al, 2014;Treder, 2010). In this paper we take the view that such grouping processes also contribute much to the understanding of urban patterns from remotely sensed images by human observers.…”
Section: Gestalt and Knowledgementioning
confidence: 99%
“…Psychologists measured that e.g. mirror symmetry is a very fast and important grouping mechanism for pictorial data in human observers, see (Sassi et al, 2014;Treder, 2010). In this paper we take the view that such grouping processes also contribute much to the understanding of urban patterns from remotely sensed images by human observers.…”
Section: Gestalt and Knowledgementioning
confidence: 99%
“…The neural correlates of tactile symmetry detection in blind and sighted individuals is also reviewed in light of available knowledge on the neural underpinnings of visual symmetry detection. An in-depth discussion of models of visual symmetry detection is beyond the scope of this review, and it has already been covered in previous work (e.g., [1,15]). The experimental paradigms used across various studies will be described in general terms to ensure that results are understandable (the reader can find methodological details in the original empirical works).…”
Section: Introductionmentioning
confidence: 99%
“…Not only are human faces and bodies symmetric, but most other living organisms (such as animals, trees, flowers and crystals) have at least one axis of symmetry, as do manufactured items, such as tools and buildings (for a recent review, see [1]). Psychophysical experiments mainly employing simple shapes or dense dot patterns as stimuli have shown that symmetry can be detected extremely quickly (within a few tens of milliseconds) and in an automatic (i.e., not mediated by a conscious cognitive effort; see [1] for review), pre-attentive manner [2][3][4]. Symmetry acts as a grouping principle of perceptual organization [5]: elements sharing symmetry relations tend to be aggregated, thus facilitating figure-ground segregation.…”
Section: Introductionmentioning
confidence: 99%
“…It has long been postulated that vertical mirror symmetry at the point of fixation has a special status due to the corresponding bilateral symmetry in the human visual system [5,6]. Nevertheless, mirror symmetry detection is still possible with different symmetry axes and at locations throughout the visual field (for comprehensive reviews of the literature, see [7][8][9]). …”
Section: Introductionmentioning
confidence: 99%